Implementation of Inclusive Student Character in Boarding School Culture-Based Learning at Darul Aziziyah Amilin Integrated Islamic Middle School in Subulussalam City - Hermalinda, Hermalinda; Kasmini, Lili; Zahraini, Zahraini; Akmaluddin, Akmaluddin (FKIP - Universitas Riau, 2025)
Moral degradation among students in Indonesia, especially during adolescence, demands an educational approach that fosters inclusive character and cultural values. This study aims to describe and analyze the implementation of inclusive character education in students through culture-based learning at Darul Aziziyah Amilin Integrated Islamic Junior High School in Subulussalam City. This qualitative study uses a descriptive approach with data collection through interviews, observation, documentation, and focus group discussions. This study involved six key informants: the principal, student coordinator, curriculum coordinator, and classroom teachers. The research findings indicate that inclusive character education is implemented by integrating the values of inclusivity and cultural respect into the learning process. This is realized through the creation of an inclusive classroom environment, the integration of local wisdom into teaching materials, and the implementation of intra- and extracurricular programs that emphasize tolerance, cooperation, and empathy. Learning is student-centered and encourages a cooperative, collaborative, and active approach. Despite facing challenges such as limited parental involvement and time constraints, the school consistently strives to improve quality through regular evaluation and communication. It can be concluded that inclusive character education supported by culture-based strategies effectively fosters moral development and social awareness among students in the context of boarding schools.